Pengaruh Penerapan Model Pembelajaran Grammar Translation Method (GTM) dalam Upaya Meningkatkan Kemampuan Nahu Mahasiswa UPI - Yusuf Ali Tantowi; Maman Abdurrahman; Renaldi Supriadi; Nurlatifah (Taqdir, 2024)
The use of learning models is one of the factors that determines students' learning success. If the learning model used is appropriate, it can arouse students' interest in studying the material being taught, thereby influencing the quality of learning outcomes. This research was motivated by the lack of motivation of UPI Arabic language education students in learning nahu. So educators must be able to apply appropriate learning methods so that students' learning motivation and learning outcomes increase. Therefore, researchers will apply the GTM model in learning nahu. The research method used is the Classroom Action Research (PTK) method. The aim of this research is to: 1) determine students' nahu mastery abilities before using the GTM method; and (2) determine students' ability to master nahu after using the GTM method. The results of classroom action research using the GTM model were carried out in 1 cycle, the results obtained were; 1) Students' knowledge abilities are "unsatisfactory", this can be seen from the low daily scores of students before implementing the GTM model; 2) Students' knowledge ability increased after implementing the GTM model with a percentage of 90%.